Hubungan Koordinasi Mata-Tangan dengan Ketepatan Lay-Up Tangan Non-Dominan pada Pemain Basket - Rio Haikal Yakini; Muhammad Sazeli Rifki; Fahd Mukhtarsyaf; Donal Syafrianto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study examined the relationship between hand-eye coordination and non-dominant-hand lay-up accuracy among basketball players at the Faculty of Sport Sciences, Universitas Negeri Padang. A quantitative correlational design was employed. The population comprised 45 players, while 30 active and physically healthy players were selected through purposive sampling. Hand-eye coordination was measured using a 30-second wall toss test, and non-dominant-hand lay-up accuracy was assessed through ten attempts. The data were analyzed using descriptive statistics, the Lilliefors normality test, and Product Moment correlation at the 0.05 significance level. The mean hand-eye coordination score was 16.8 with a standard deviation of 2.5, whereas the mean lay-up accuracy score was 7.6 with a standard deviation of 1.1. The correlation analysis produced an observed coefficient of 0.012, which was lower than the critical value of 0.361. Therefore, no significant relationship was found between hand-eye coordination and non-dominant-hand lay-up accuracy. These findings indicate that specific technical mastery, practice experience, physical condition, motor learning, and psychological factors should be considered when developing non-dominant-hand lay-up performance.